IFIT3 activation significantly contributes to HIV-1-associated neurodegenerative disorder-mediated neuroinflammation - Das, Ranjit Kumar; Sahoo, Nirakar; Roy, Deepa; Xu, Chun; Galarza, Jose; Garza, Maria Camila Mejia; Rodrigo, Hansapani; Duttaroy, Asim K.; Roy, Upal (Frontiers in Immunology, 2025)
IntroductionThe advent of effective combination antiretroviral therapy (cART) has significantly improved HIV-1 treatment, saving millions of lives. However, HAND remains a concern, particularly among aging individuals with HIV-1. The mechanisms underlying HAND are not well understood.MethodsThis study investigated the role of interferon-induced protein with tetratricopeptide repeats 3 (IFIT3) and its upstream regulator, signal transducer, and activator of transcription 1 (STAT1), in HAND pathology. Using the SH-SY5Y neuroblastoma cell line and HIV-infected humanized mice, we examined the effects of the cART drugs, HIV Tat protein, and HIV-1 virus on STAT1 and IFIT3 expression.ResultsThe results showed that HIV-1 exposure significantly upregulated STAT1 and IFIT3, contributing to neuroinflammation.DiscussionThis study identified IFIT3 as a critical molecular marker for HAND, suggesting its potential as a therapeutic target and offering new insights into disease pathology and treatment strategies.